The synthesis of active pharmaceutical ingredients (APIs) using continuous flow chemistry - Baumann, Marcus; Baxendale, Ian R. (Beilstein Journal of Organic Chemistry, 2015)
The implementation of continuous flow processing as a key enabling technology has transformed the way we conduct chemistry and has expanded our synthetic capabilities. As a result many new preparative routes have been designed towards commercially relevant drug compounds achieving more efficient and reproducible manufacture. This review article aims to illustrate the holistic systems approach and diverse applications of flow chemistry to the preparation of pharmaceutically active molecules, demonstrating the value of this strategy towards every aspect ranging from synthesis, in-line analysis and purification to final formulation and tableting. Although this review will primarily concentrate on large scale continuous processing, additional selected syntheses using micro or meso-scaled flow reactors will be exemplified for key transformations and process control. It is hoped that the reader will gain an appreciation of the innovative technology and transformational nature that flow chemistry can leverage to an overall process.
Keywords: continuous processing; flow synthesis; in-line analysis; manufacture; pharmaceuticals; scalability

(untitled) - Ingham, R. J.; Battilocchio, C.; Fitzpatrick, D. E.; Sliwinski, E.; Hawkins, J. M.; Ley, S. V. (Angew. Chem., Int. Ed., 2015)

(untitled) - Wegner, J.; Ceylan, S.; Kirschning, A. (Adv. Synth. Catal., 2012)

(untitled) - Jensen, K. F.; Reizman, B. J.; Newman, S. G. (Lab Chip, 2014)

(untitled) - Yoshida, J.; Takahasi, Y.; Nagaki, A. (Chem. Commun., 2013)

(untitled) - Hessel, V.; Kralisch, D.; Kockmann, N.; Noël, T.; Wang, Q. (ChemSusChem, 2013)

(untitled) - Plouffle, P.; Macchi, A.; Roberge, D. M. (Org. Process Res. Dev., 2014)

(untitled) - Baxendale, I. R. (J. Chem. Technol. Biotechnol., 2013)

(untitled) - Baxendale, I. R.; Brocken, L.; Mallia, C. J. (Green Process. Synth., 2013)

(untitled) - Mitic, A.; Heintz, S.; Ringborg, R. F.; Bodla, V.; Woodley, J. M.; Gernaey, K. V. (Chim. Oggi, 2013)

(untitled) - Webb, D.; Jamison, J. T. (Chem. Sci., 2010)

(untitled) - Baumann, M.; Baxendale, I. R.; Ley, S. V. (Mol. Diversity, 2011)

(untitled) - Pastre, J. C.; Browne, D. L.; Ley, S. V. (Chem. Soc. Rev., 2013)

(untitled) - Yoshida, J.; Kim, H.; Nagaki, A. (ChemSusChem, 2011)

(untitled) - McQuade, D. T.; Seeberger, P. H. (J. Org. Chem., 2013)

(untitled) - Wiles, C.; Watts, P. (Green Chem., 2012)

(untitled) - Cranwell, P. B.; O’Brien, M.; Browne, D. L.; Koos, P.; Polyzos, A.; Peña-López, M.; Ley, S. V. (Org. Biomol. Chem., 2012)

(untitled) - Baumann, M.; Baxendale, I. R.; Martin, L. J.; Ley, S. V. (Tetrahedron, 2009)

(untitled) - McPake, C. B.; Sandford, G. (Org. Process Res. Dev., 2012)

(untitled) - Baumann, M.; Baxendale, I. R.; Ley, S. V.; Nikbin, N.; Smith, C. D.; Tierney, J. P. (Org. Biomol. Chem., 2008)

(untitled) - Rossi, E.; Woehl, P.; Maggini, M. (Org. Process Res. Dev., 2012)

(untitled) - Roberge, D. M.; Noti, C.; Irle, E.; Eyholzer, M.; Rittiner, B.; Penn, G.; Sedelmeier, G.; Schenkel, B. (J. Flow Chem., 2014)

(untitled) - Baxendale, I. R.; Braatz, R. D.; Hodnett, B. K.; Jensen, K. F.; Johnson, M. D.; Sharatt, P.; Sherlock, J.-P.; Florence, A. J. (J. Pharm. Sci., 2015)

(untitled) - Moore, J. S.; Jensen, K. F. (Angew. Chem., Int. Ed., 2014)

(untitled) - Lange, H.; Carter, C. F.; Hopkin, M. D.; Burke, A.; Goode, J. G.; Baxendale, I. R.; Ley, S. V. (Chem. Sci., 2011)

(untitled) - Brodmann, T.; Koos, P.; Metzger, A.; Knochel, P.; Ley, S. V. (Org. Process Res. Dev., 2012)

(untitled) - Zhang, H.; Quon, J.; Alvarez, A. J.; Evans, J.; Myerson, A. S.; Trout, B., II (Org. Process Res. Dev., 2012)

(untitled) - Newman, S. G.; Jensen, K. F. (Green Chem., 2013)

(untitled) - Zhang, Y.; Born, S. C.; Jensen, K. F. (Org. Process Res. Dev., 2014)

(untitled) - Cantillo, D.; Damm, M.; Dallinger, D.; Bauser, M.; Berger, M.; Kappe, C. O. (Org. Process Res. Dev., 2014)

(untitled) - Filipponi, P.; Ostacolo, C.; Novellino, E.; Pellicciari, R.; Gioiello, A. (Org. Process Res. Dev., 2014)

(untitled) - Gutmann, G.; Gottsponer, M.; Elsner, P.; Cantillo, D.; Roberge, D. M.; Kappe, C. O. (Org. Process Res. Dev., 2013)

(untitled) - May, S. A.; Johnson, M. D.; Braden, T. M.; Calvin, J. R.; Haeberle, B. D.; Jines, A. R.; Miller, R. D.; Plocharczyk, E. F.; Rener, G. A.; Richey, R. N.; Schmid, C. R.; Vaid, R. K.; et al. (Org. Process Res. Dev., 2012)

(untitled) - Reddy, G. S.; Reddy, N. S.; Manudhane, K.; Krisha, M. V. R.; Ramachandra, K. J. S.; Gangula, S. (Org. Process Res. Dev., 2013)

(untitled) - Martin, A. D.; Siamaki, A. R.; Belecki, K.; Gupton, B. F. (J. Flow Chem., 2015)

(untitled) - Wegner, J.; Ceylan, S.; Kirschning, A. (Chem. Commun., 2011)

(untitled) - Hartman, R. L. (Org. Process Res. Dev., 2012)

(untitled) - Page, T.; Dubina, H.; Fillipi, G.; Guidat, R.; Patnaik, S.; Poechlauer, P.; Shering, P.; Guinn, M.; McDonnell, P.; Johnston, C. (J. Pharm. Sci., 2015)

(untitled) - Malet-Sanz, L.; Susanne, F. (J. Med. Chem., 2012)

(untitled) - Hartman, R. L.; McMullen, J. P.; Jensen, K. F. (Angew. Chem., Int. Ed., 2011)

(untitled) - Gustafsson, T.; Pontén, F.; Seeberger, P. H. (Chem. Commun., 2008)

(untitled) - Gross, T.; Chou, S.; Bonneville, D.; Gross, R. S.; Wang, P.; Campopiano, O.; Ouellette, M. A.; Zook, S. E.; Reddy, J. P.; Moree, W. J.; Jovic, F.; Chopade, S. (Org. Process Res. Dev., 2008)

(untitled) - Tanaka, K.; Motomatsu, S.; Koyama, K.; Tanaka, S.; Fukase, K. (Org. Lett., 2007)

(untitled) - Riva, E.; Gagliardi, S.; Mazzoni, C.; Passarella, D.; Rencurosi, A.; Vigo, D.; Martinelli, M. (J. Org. Chem., 2009)

(untitled) - Schwalbe, T.; Kadzimirsz, D.; Jas, G. (QSAR Comb. Sci., 2005)

(untitled) - LaPorte, T. L.; Hamedi, M.; DePue, J. S.; Shen, L.; Watson, D.; Hsieh, D. (Org. Process Res. Dev., 2008)

(untitled) - Ni, X.; Mackley, M. R.; Harvey, A. P.; Stonestreet, P.; Baird, M. H. I.; Rao, N. V. R. (Chem. Eng. Res. Des., 2003)

(untitled) - Ricardo, C.; Xiongwei, N. (Org. Process Res. Dev., 2009)

(untitled) - Bogdan, A. R.; Poe, S. L.; Kubis, D. C.; Broadwater, S. J.; McQuade, D. T. (Angew. Chem., Int. Ed., 2009)

U.S. Patent - Lindley, D. D.; Curtis, T. A.; Ryan, T. R.; de la Garza, E. M.; Hilton, C. B.; Kenesson, T. M. (Process for the production of 4'-isobutylacetophenone, 1991)

U.S. Patent - Elango, V.; Murphy, M. A.; Smith, B. L.; Davenport, K. G.; Mott, G.; Zey, E. G.; Moss, G. L. (Method for producing ibuprofen, 1991)

(untitled) - Sonowane, H. R.; Bellur, N. S.; Kulkarni, D. G.; Ayyangar, N. R. (Tetrahedron, 1994)

(untitled) - Snead, D. R.; Jamison, T. F. (Angew. Chem., Int. Ed., 2015)

(untitled) - Hopkin, M. D.; Baxendale, I. R.; Ley, S. V. (Chem. Commun., 2010)

(untitled) - Hopkin, M. D.; Baxendale, I. R.; Ley, S. V. (Org. Biomol. Chem., 2013)

(untitled) - Deadman, B. J.; Hopkin, M. D.; Baxendale, I. R.; Ley, S. V. (Org. Biomol. Chem., 2013)

(untitled) - Qian, Z.; Baxendale, I. R.; Ley, S. V. (Synlett, 2010)

(untitled) - Qian, Z.; Baxendale, I. R.; Ley, S. V. (Chem. – Eur. J., 2010)

(untitled) - Riva, E.; Gagliardi, S.; Martinelli, M.; Passarella, D.; Vigo, D.; Rencurosi, A. (Tetrahedron, 2010)

(untitled) - Venturoni, F.; Nikbin, N.; Ley, S. V.; Baxendale, I. R. (Org. Biomol. Chem., 2010)

(untitled) - Ahmed-Omer, B.; Sanderson, A. J. (Org. Biomol. Chem., 2011)

(untitled) - Lévesque, F.; Seeberger, P. H. (Angew. Chem., Int. Ed., 2012)

(untitled) - Kopetzki, D.; Lévesque, F.; Seeberger, P. H. (Chem. – Eur. J., 2013)

(untitled) - Knowles, J. P.; Elliott, L. D.; Booker-Milburn, K. I. (Beilstein J. Org. Chem., 2012)

(untitled) - Cludius-Brandt, S.; Kupracz, L.; Kirschning, A. (Beilstein J. Org. Chem., 2013)

(untitled) - Elliott, L. D.; Knowles, J. P.; Koovits, P. J.; Maskill, K. G.; Ralph, M. J.; Lejeune, G.; Edwards, L. J.; Robinson, R. I.; Clemens, I. R.; Cox, B.; Pascoe, D. D.; Koch, G.; et al. (Chem. – Eur. J., 2014)

(untitled) - Gilmore, K.; Vukelić, S.; McQuade, D. T.; Koksch, B.; Seeberger, P. H. (Org. Process Res. Dev., 2014)

(untitled) - Gilmore, K.; Kopetzki, D.; Lee, J. W.; Horváth, Z.; McQuade, D. T.; Seidel-Morgenstern, A.; Seeberger, P. H. (Chem. Commun., 2014)

(untitled) - Fan, X.; Sans, V.; Yaseneva, P.; Plaza, D. D.; Williams, J.; Lapkin, A. (Org. Process Res. Dev., 2012)

(untitled) - Caron, A.; Hernandez-Perez, A. C.; Collins, S. K. (Org. Process Res. Dev., 2014)

(untitled) - Šterk, D.; Jukič, M.; Časar, Z. (Org. Process Res. Dev., 2013)

(untitled) - Gustafsson, T.; Sörensen, H.; Pontén, F. (Org. Process Res. Dev., 2012)

(untitled) - LaPorte, T. L.; Spangler, L.; Hamedi, M.; Lobben, P.; Chan, S. H.; Mushlehiddinoglu, J.; Wang, S. S. Y. (Org. Process Res. Dev., 2014)

(untitled) - Dyer, U. C.; Henderson, D. A.; Mitchell, M. B.; Tiffin, P. D. (Org. Process Res. Dev., 2002)

(untitled) - Pellegatti, L.; Sedelmeier, J. (Org. Process Res. Dev., 2015)

(untitled) - Johnson, M. D.; May, S. A.; Calvin, J. R.; Remacle, J.; Stout, J. R.; Diseroad, W. D.; Zaborenko, N.; Haeberle, B. D.; Sun, W.-M.; Miller, M. T.; Brennan, J. (Org. Process Res. Dev., 2012)

(untitled) - Franckevičius, V.; Knudsen, K. R.; Ladlow, M.; Longbottom, D. A.; Ley, S. V. (Synlett, 2006)

(untitled) - Baumann, M.; Baxendale, I. R.; Ley, S. V. (Synlett, 2010)

(untitled) - Bryan, M. C.; Wernick, D.; Hein, C. D.; Petersen, J. V.; Eschelbach, J. W.; Doherty, E. M. (Beilstein J. Org. Chem., 2011)

(untitled) - Baumann, M.; Baxendale, I. R.; Hornung, C. H.; Ley, S. V.; Rojo, M. V.; Roper, K. A. (Molecules, 2014)

(untitled) - Buisson, B.; Donegan, S.; Wray, D.; Parracho, A.; Gamble, J.; Caze, P.; Jorda, J.; Guermeur, C. (Chim. Oggi, 2009)

(untitled) - Irfan, M.; Glasnov, T. N.; Kappe, C. O. (ChemSusChem, 2011)

(untitled) - Miller, P. W.; Long, N. J.; de Mello, A. J.; Vilar, R.; Passchier, J.; Gee, A. (Chem. Commun., 2006)

(untitled) - Csajági, C.; Borcsek, B.; Niesz, K.; Kovács, I.; Székelyhidi, Z.; Bajkó, Z.; Ürge, L.; Darvas, F. (Org. Lett., 2008)

(untitled) - Brzozowski, M.; O’Brien, M.; Ley, S. V.; Polyzos, A. (Acc. Chem. Res., 2015)

(untitled) - Pastre, J. C.; Browne, D. L.; O’Brien, M.; Ley, S. V. (Org. Process Res. Dev., 2013)

(untitled) - Snead, D. R.; Jamison, T. F. (Chem. Sci., 2013)

(untitled) - Zhang, P.; Russell, M. G.; Jamison, T. F. (Org. Process Res. Dev., 2014)

(untitled) - Kopach, M. E.; Murray, M. M.; Braden, T. M.; Kobierski, M. E.; Williams, O. L. (Org. Process Res. Dev., 2009)

(untitled) - Palde, P. B.; Jamison, T. F. (Angew. Chem., Int. Ed., 2011)

(untitled) - Delville, M. M. E.; Nieuwland, P. J.; Janssen, P.; Koch, K.; van Hest, J. C. M.; Rutjes, F. P. J. T. (Chem. Eng. J., 2011)

(untitled) - Borukhova, S.; Noël, T.; Metten, B.; de Vos, E.; Hessel, V. (ChemSusChem, 2013)

(untitled) - Myers, R. M.; Shearman, J. W.; Kitching, M. O.; Ramos-Montoya, A.; Neal, D. E.; Ley, S. V. (ACS Chem. Biol., 2009)

(untitled) - Battilocchio, C.; Deadman, B. J.; Nikbin, N.; Kitching, M. O.; Baxendale, I. R.; Ley, S. V. (Chem. – Eur. J., 2013)

(untitled) - Deadman, B. J.; Ley, S. V.; Browne, D. L.; Baxendale, I. R.; Ley, S. V. (Chem. Eng. Technol., 2015)

(untitled) - Battilocchio, C.; Baxendale, I. R.; Biava, M.; Kitching, M. O.; Ley, S. V. (Org. Process Res. Dev., 2012)

(untitled) - Baxendale, I. R.; Hornung, C.; Ley, V.; de Mata Muñoz Molina, J.; Wikstroöm, A. (Aust. J. Chem., 2012)

(untitled) - Glasnov, T. N.; Kappe, C. O. (Chem. – Eur. J., 2011)

(untitled) - Baxendale, I. R.; Pitts, M. R. (Chim. Oggi, 2006)

(untitled) - Glasnov, T. N.; Kappe, C. O. (Macromol. Rapid Commun., 2007)

(untitled) - Baxendale, I. R.; Hayward, J. J.; Ley, S. V. (Comb. Chem. High Throughput Screening, 2007)

(untitled) - Schmink, J. R.; Kormos, C. M.; Devine, W. G.; Leadbeater, N. E. (Org. Process Res. Dev., 2010)

(untitled) - Celan, S.; Coutable, L.; Wegner, J.; Kirschning, A. (Chem. – Eur. J., 2011)

(untitled) - Kirschning, A.; Kupracz, L.; Hartwig, J. (Chem. Lett., 2012)

(untitled) - Hartwig, J.; Ceylan, S.; Kupracz, L.; Coutable, L.; Kirschning, A. (Angew. Chem., Int. Ed., 2013)

(untitled) - Kupracz, L.; Kirschning, A. (Adv. Synth. Catal., 2013)

(untitled) - Murray, P. R. D.; Browne, D. L.; Pastre, J. C.; Butters, C.; Guthrie, D.; Ley, S. V. (Org. Process Res. Dev., 2013)

(untitled) - Krtschil, U.; Hofmann, C.; Löb, P.; Schütt, C.; Schorcht, P.; Streuber, M. (Green Process. Synth., 2013)

(untitled) - Guetzoyan, L.; Nikbin, N.; Baxendale, I. R.; Ley, S. V. (Chem. Sci., 2013)

(untitled) - Desai, B.; Dixon, K.; Farrant, E.; Feng, Q.; Gibson, K. R.; van Hoorn, W. P.; Mills, J.; Morgan, T.; Parry, D. M.; Ramjee, M. K.; Selway, C. N.; Tarver, G. J.; et al. (J. Med. Chem., 2013)

(untitled) - Polster, C. S.; Cole, K. P.; Burcham, C. L.; Campbell, B. M.; Frederick, A. L.; Hansen, M. M.; Harding, M.; Heller, M. R.; Miller, M. T.; Phillips, J. L.; Pollock, P. M.; Zaborenko, N. (Org. Process Res. Dev., 2014)

(untitled) - White, T. D.; Berglund, K. D.; McClary Groh, J.; Johnson, M. D.; Miller, R. D.; Yates, M. H. (Org. Process Res. Dev., 2012)

(untitled) - Mascia, S.; Heider, P. L.; Zhang, H.; Lakerveld, R.; Benyahia, B.; Barton, P. I.; Braatz, R. D.; Cooney, C. L.; Evans, J. M. B.; Jamison, T. F.; Jensen, K. F.; Myerson, A. S.; et al. (Angew. Chem., Int. Ed., 2013)